Xanthomonas leaf blight of onion: biology, epidemiology, and management - Gent, David H., author; Schwartz, Howard F., advisor; Brick, Mark A., committee member; Bartolo, Michael E., committee member; Leach, Jan E., committee member (Colorado State University. Libraries, 2004)
Xanthomonas leaf blight of onion is a yield limiting disease of onion in Colorado. Sustainable management strategies have not been developed because basic elements of pathogen and disease biology are unknown. The objective of this dissertation was to develop sustainable Xanthomonas leaf blight management strategies from a basic understanding of pathogen and disease biology. The pathogenic, phenotypic, and pathogenic diversity of forty-nine onion Xanthomonas strains were determined. Multiplication of onion Xanthomonas strain R-O177 was not different than X. axonopodis pv. phaseoli in dry bean, but typical common bacterial blight disease symptoms were absent. All strains were sensitive to 100 μg/ml CUSO4, ZnSO4, or streptomycin sulfate. Logistic regression of fatty acid and substrate utilization profiles classified 69% of strains into their geographical region of origin. Rep-DNA fingerprinting revealed five genotype groups within onion Xanthomonas strains. Based upon pathogenicity to onion and genomic fingerprinting, the onion Xanthomonas strains examined in this study are X. axonopodis pv. allii (Xaa). X aa inoculum sources are unknown, but this knowledge is essential to disease management. To identify these sources, epiphytic xanthomonad populations on weed, volunteer onion, and leguminous plants were quantified at five locations in eastern Colorado over 2003 and 2004. Irrigation water and crop debris were sampled for Xaa populations in experimental plots near Fort Collins and Rocky. Xaa was recovered from irrigation water, weed, volunteer onion, and leguminous plants. The bacterium survived in unincorporated crop debris, but not in buried debris. Epiphytic populations of Xaa (102 to 103) survived on dry bean and lentil under field conditions; epiphytic X. axonopodis pv. phaseoli were recovered from onion following dry bean. Elimination of these inoculum sources should reduce Xanthomonas leaf blight losses. Alternatives to copper bactericides are needed to reduce use of high-risk pesticides. Studies evaluated alternative treatments and determined the critical period for conventional copper applications. Acibenzolar-S-methyl was as effective as copper applications in suppressing Xathomonas leaf blight in field trials. The critical period ranged from1 to 2 weeks before bulb initiation. Adoption of disease forecasting and novel chemical treatments such as acibenzolar-S-methyl may reduce copper bactericide use for Xanthomonas leaf blight management in Colorado.
Missing page 131.
Keywords: plant pathology